Bacteria associated with tunicate, Polycarpa aurata, from Lease Sea, Maluku, Indonesia exhibiting anti-multidrug resistant bacteria - DIAH AYUNINGRUM; RHESI KRISTIANA; AYUNDA AINUN NISA; SEPTHY KUSUMA RADJASA; SAKTI IMAM MUCHLISSIN; OCKY KARNA RADJASA; AGUS SABDONO; AGUS TRIANTO (Society for Indonesian Biodiversity, 2019)
Abstract. Ayuningrum D, Kristiana R, Nisa AA, Radjasa SK, Muchlissin SI, Radjasa OK, Sabdono A, Trianto A. 2019. Bacteria associated with tunicate, Polycarpa aurata, from Lease Sea, Maluku, Indonesia exhibiting anti-multidrug resistant bacteria. Biodiversitas 20: 956-964. Tunicate is a rich secondary metabolites producer with various biological activities whether as an original producer or produced by the associated microorganisms. In this study, a total of 11 tunicate specimens were identified as Polycarpa aurata with four color variations based on morphological characteristic and COI gene identification and BLAST analysis. The P. aurata associated-bacteria were isolated and tested for antimicrobial activity against multi-drug resistant (MDR) bacteria. A total of 86 axenic isolates were successfully purified. Furthermore, nine isolates (10.5%) exhibited antibacterial activity on preliminary screening. Nine prospective isolates were fermented in respective medium (Zobell 2216, modified M1 or modified ISP2 media) then extracted using ethyl acetate. The ethyl acetate extracts from liquid fermentation were tested against MDR Escherichia coli, MDR Bacillus cereus, Methicillin-Resistant Staphylococcus aureus (MRSA) and Methicillin-Sensitive and Staphylococcus aureus (MSSA). As a result, seven isolates (8.1%) still retained the activity at the extract concentration 150 µg/disk. Molecular analysis based on 16S rDNA sequencing revealed the most active isolates, TSB 47, TSC 10 and TSB 34 identified as Bacillus tropicus, Vibrio alginolyticus and Virgibacillus massiliensis, with BLAST homology 99%.